Dictators and dictatorships : understanding authoritarian regimes and their leaders - Ezrow, Natasha M. (Continuum, 2011)
Authoritarian politics : typologies -- The causes of dictatorship -- The survival of authoritarian regimes : strategies and trends -- The survival of authoritarian leaders : strategies and trends -- Coups -- Dictatorships and political gridlock -- Dictatorships and the economy -- Dictatorships and international conflict -- Military dictatorships in Latin America and beyond -- Single-party dictatorships in Eastern Europe, Asia, and beyond -- Personalist dictatorships in sub-saharan Africa and beyond -- Monarchies in the Middle East and beyond -- Hybrid dictatorships